Lactobacillus suantsaicola sp. nov. and Lactobacillus suantsaiihabitans sp. nov., isolated from suan-tsai, a traditional fermented mustard green product of Taiwan. Issue 5 (14th June 2019) - Lin, Shih-Ting; Wang, Li-Ting; Wang, Hsing-Min; Tamura, Tomohiko; Mori, Koji; Huang, Lina; Watanabe, Koichi
Abstract : Four Gram-stain-positive strains, R7 T, R11, R19 T and R27, were isolated from suan-tsai, a traditional fermented mustard green product of Taiwan. Cells were rod-shaped, non-motile, non-haemolytic, asporogenous, facultatively anaerobic, heterofermentative, and did not exhibit catalase and oxidase activities. Comparative analyses of 16S rRNA, pheS and rpoA gene sequences demonstrated that these novel strains were members of the genus Lactobacillus . 16S rRNA and the concatenated pheS and rpoA gene sequence similarities between strains R7 T and R11, and strains R19 T and R27 were very high (>99.8 % similarity), respectively. On the basis of 16S rRNA gene sequence similarities, the type strains of Lactobacillus paralimentarius (98.5 %), Lactobacillus kimchii (98.5 %), Lactobacillus alimentarius (98.1 %) and Lactobacillus bobalius (98.1 %) were the closest neighbours to strains R7 T and R11, and the type strains of Lactobacillus brevis (98.9 %), Lactobacillus cerevisiae (98.4 %), Lactobacillus hammesii (98.4 %), Lactobacillus koreensis (98.4 %) and Lactobacillus yonginensis (98.0 %) were the closest neighbours to strains R19 T and R27, respectively. The average nucleotide identity values of R7 T and R19 T with the closely related type strains were 78.9–80.1% and 75.7–80.5 %, respectively. The digital DNA–DNA hybridization values were 22.8–23.6% and 21.0–23.1 %, respectively. Phenotypic and genotypic test results demonstrated that these strains represent two novel species of the genus Lactobacillus, for which the name Lactobacillus suantsaicola sp. nov. (R7 T =BCRC 81127 T =NBRC 113530 T ) and Lactobacillus suantsaiihabitans sp. nov. (R19 T =BCRC 81129 T =NBRC 113532 T ) are proposed.